2011
DOI: 10.5539/ijbm.v6n6p207
|View full text |Cite
|
Sign up to set email alerts
|

Are Nigeria SMEs Effectively Utilizing ICT?

Abstract: This paper investigates reasons for the non-utilization of ICT by SMEs in Nigeria using a survey of 180 SMEs. The results of the study indicates that majority of Nigeria SMEs utilizes basic ICT such as word processing, fixed landlines, printers and fax machines but rarely use the computer for advance functions such as business analysis, planning and decision making. However, there are key factors that inhibit these SMEs from effectively utilizing ICT in their various businesses. The survey suggests that electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…Barriers to adoption can take various forms. Examples include a lack of organizational readiness (Grandon & Pearson, 2004;Lacovou et al, 1995), incompatibility (Azad & Hasan, 2011;Beatty et al, 2001;Rogers, 1995), complexity (Thomas et al, 2011;Thong, 1999), lack of visibility (Moore & Benbasat, 2001), high costs (Alam et al, 2011), security concerns (Voges & Pulakanam, 2011;Zaied, 2012), lack of customer readiness (Scupola, 2009), lack of skilled labour (Lawrence & Tar, 2010;Samoilenko & Osei-Bryson, 2008), and lack of infrastructure readiness (Apulu & Ige, 2011). Furthermore, TAM shows that perceiving a system as easy to use leads to the perception that it is useful to the business, which suggests that ease of use is a determinant of perceived usefulness (Davis et al, 1989;Riemenschneider et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Barriers to adoption can take various forms. Examples include a lack of organizational readiness (Grandon & Pearson, 2004;Lacovou et al, 1995), incompatibility (Azad & Hasan, 2011;Beatty et al, 2001;Rogers, 1995), complexity (Thomas et al, 2011;Thong, 1999), lack of visibility (Moore & Benbasat, 2001), high costs (Alam et al, 2011), security concerns (Voges & Pulakanam, 2011;Zaied, 2012), lack of customer readiness (Scupola, 2009), lack of skilled labour (Lawrence & Tar, 2010;Samoilenko & Osei-Bryson, 2008), and lack of infrastructure readiness (Apulu & Ige, 2011). Furthermore, TAM shows that perceiving a system as easy to use leads to the perception that it is useful to the business, which suggests that ease of use is a determinant of perceived usefulness (Davis et al, 1989;Riemenschneider et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 97%
“…An in-depth literature review has revealed numerous variables that have been examined previously, as illustrated in Table 1. Variables concerning the perceived benefits of adoption range from improving customer satisfaction (Apulu & Ige, 2011) and staff satisfaction (Harindranath, Dyerson, & Barnes, 2008) or competitive advantage (Estebanez, 2010), to supporting effective re-intermediation (Alvarex et al, 2007), a benefit that is particularly relevant for the travel trade. Inevitably, while there are many benefits to adoption, there are also perceived barriers, including limited resource availability (Skoko, Ceric, & Huang, 2008) and a lack of staff with IT/travel skills (Lawrence & Tar, 2010).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Thus organizations from developed economies have attained a significant level of adoption leaving their counter parts from developing countries far behind and still struggling with its implementation challenges. Researchers examining the adoption barriers from developing country perspectives such as Nigeria (Apulu & Latham, 2009;Apulu & Ige, 2011;Ibironke et al, 2011;Eze et al, 2013), India (Ahuja et al, 2009), Malaysia (Jafari et al, 2006;Mui et al, 2002), Egypt (Aboelmaged, 2014), Iran ( Sidawi et al, 2012), Brazil (Goedhuys & Veugelers, 2012), South Africa (Ogunyemi, & Johnston, 2012), Jordan (El-Mashaleh, 2007) have emphasized leadership (top management/CEOs) ineffectiveness as the major constrain to successful ICT adoption. Similarly, other studies (Martin & Hug, 2007;Ihua, 2009;Jung et al, 2003) have identified top management strategies toward managing employee behavioural change as another significant barrier to embracing technological change.…”
Section: Introductionmentioning
confidence: 99%
“…The major problems facing SMEs in IT adoption as revealed by the study are: lack of infrastructural facilities, corruption, cost of implementation, lack of funds, lack of awareness among owners-managers, lack of skills and training, cultural factors, lack of government policies that support ICT adoption in SMEs and electricity constraints. Furthermore, [13] investigates the reasons for non-utilization of ICT by SMEs in Nigeria and found that the inhibiting factors are electricity, lack of infrastructure, poor service from ISP provider, lack of education, lack of support from government and banks and cost of training and maintenance. The study confirmed the most of the major problems of IT adoption as reported in most literatures from Nigerian context.…”
Section: The Causes Of Low It Adoption Among Nigerian Constructimentioning
confidence: 99%